Syndrome of inappropriate antidiuretic hormone secretion in neonates with birth asphyxia at tertiary care centre - Gagandeep, Vijayalaxmi; S., Vidhya P. (International Journal of Contemporary Pediatrics, 2019)
Background: Syndrome of inappropriate antidiuretic hormone is an important metabolic complication of perinatal asphyxia. This study aims to study the occurrence of syndrome of inappropriate antidiuretic hormone in different grades of perinatal asphyxia and to find out the correlation of syndrome of inappropriate antidiuretic hormone to gestational age and birth weight in birth asphyxiated babies. Methods: It was a hospital-based cohort study. 50 neonates with different grades of asphyxia were enrolled in the study and 50 controls were taken. Syndrome of inappropriate antidiuretic hormone was diagnosed based on calculated plasma osmolality, serum and urine sodium, urine specific gravity and analyzed with different grades of birth asphyxia and birthweight and gestation age. Results: The occurrence of SIADH in birth asphyxiated babies was 26% and none of the babies in control group developed SIADH. The occurrence was more in the severely asphyxiated babies (53.8%), followed by moderate (30.8%) and then mildly asphyxiated babies (15.4%). Hyponatremia was seen in 26% of birth asphyxiated babies and can be used as a marker of SIADH. In relation to gestation age and birth weight there was no statistically significant correlation between SIADH and different grades of asphyxia. Mortality was high among the neonates who developed SIADH. Conclusions: The occurrence of SIADH was 26% in asphyxiated neonates and high in severe asphyxia and gestation age and birth weight beard no significant co relation.